Factors Affecting Women’s Estate Planning Needs: A Quantitative Survey - TabaanAlenezi, Omar; Mlama, Shereen (Journal of Global Economy, Business and Finance, 2025)
Estate planning is arrangement for the management and distribution of one's assets and wealth after death or in the event of incapacity. It involves creating legally binding documents such as wills, trusts, powers of attorney, and advance directives to ensure that an individual's wishes regarding their property, financial affairs, and healthcare decisions are carried out according to their preferences. It is essential for individuals of all ages and income levels to engage in estate planning to protect themselves and their families in the event of incapacity or death. Consulting with legal and financial professionals can help individuals create a comprehensive estate plan tailored to their specific needs and goals. This study investigates the factors like longer life expectancy, wage gap and career interruptions, Asset ownership and control, Family dynamics and care giving responsibilities, protecting children and heirs that contribute to the necessity for estate planning among women where surveys will be conducted to gather data from a diverse sample of 216 women. The study will examine demographic factors such as age, marital status, educational level, and family structure and conduct the t - test to determine their influence of different on women's estate planning needs. By addressing these factors, stakeholders can develop targeted strategies and educational resources to empower women to make informed decisions about their financial futures and legacy planning.